1987
DOI: 10.1144/gsl.sp.1987.028.01.04
|View full text |Cite
|
Sign up to set email alerts
|

The extensional strength of the continental lithosphere: its dependence on geothermal gradient, and crustal composition and thickness

Abstract: Summary The response of lithosphere to an applied tectonic tensile force and the resulting stress distribution with depth has been investigated using a mathematical model incorporating the elastic, plastic and brittle behaviour of lithospheric material. Lithospheric strength is shown to be primarily controlled by lithospheric rheology and as a consequence is critically dependent on geothermal gradient and lithospheric composition. The rheologies of the upper crust, lower crust and mantle are assumed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
212
1
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(228 citation statements)
references
References 17 publications
14
212
1
1
Order By: Relevance
“…Studies on lithospheric strength in a laterally homogeneous undeformed lithosphere have been dealt with in a number of studies (e.g. Kohlstedt, Evans & Mackwell, 1995;Hirth & Kohlstedt, 1996;Kusznir & Park, 2002;Van Wijk & Cloetingh, 2002;Jackson et al 2008). In brief, these authors concluded that increased heat flow and high rates of spreading generally resulted in a net weakening of the lithosphere and conversely, very slow spreading rates and low heat flows could result in a net strengthening.…”
Section: E Lithospheric Strengthmentioning
confidence: 99%
“…Studies on lithospheric strength in a laterally homogeneous undeformed lithosphere have been dealt with in a number of studies (e.g. Kohlstedt, Evans & Mackwell, 1995;Hirth & Kohlstedt, 1996;Kusznir & Park, 2002;Van Wijk & Cloetingh, 2002;Jackson et al 2008). In brief, these authors concluded that increased heat flow and high rates of spreading generally resulted in a net weakening of the lithosphere and conversely, very slow spreading rates and low heat flows could result in a net strengthening.…”
Section: E Lithospheric Strengthmentioning
confidence: 99%
“…Total crustal thickness varies between 10 and 15 km in the forearc (east to the outer arc high and north of 28° N), but may reach 20 km beneath the arc. Thicker crust (which is Theologically weak compared to the mantle) and higher heat flow have been shown to weaken the lithosphere (Vink et al, 1984;Steckler and ten Brink, 1986;Kuznir and Park, 1987). I therefore infer that the frontal arc volcanoes create a linear zone of lithospheric weakness that controls the location of rifting (B.…”
Section: Locus and Duration Of Riftingmentioning
confidence: 99%
“…Glazner and Bartley (1985) suggested that a balance between radioactive decay and denudation rates of a continental crust duplicated by thrusting may cause strong softening which enhances post-thrusting extension. Moreover, the lower strength of the continental crust in relation to mantle material suggests that thickened continental lithosphere is weaker than normal thickness continental and oceanic lithospheres (Brace andKohlstedt 1980, Kuznir andPark 1987), and hence it will be able to flow under its own weight (Molnar and Lyon-Caen 1988). So, if we consider the strong preexistent anisotropy due to structural discontinuities formed during convergence, and the rheological controls that lower the strength of duplicated continental crust (Teyssier and Vanderhaeghe 2001), the orogenic belts are suitable sites for extensional flow regimes (Norton 1986).…”
Section: Introductionmentioning
confidence: 99%